Mean Platelet Volume in the Diagnosis of Acute Appendicitis in the Pediatric Population: A Systematic Review and Meta-Analysis - Krishnan Nellai; Anand Sachnit; Pakkasjarvi Niklas; Bajpai Minu; Dhua Anjan Kumar; Yadav Devendra Kumar (MDPI, 2022)
Background: Mean Platelet Volume (MPV) has been suggested as a biomarker for acute appendicitis (AA) in the adult population. The utility of MPV in pediatric AA remains vague. This systematic review and meta-analysis aimed to systematically summarize and compare all relevant data on MPV as a diagnostic biomarker for AA in children.
Methods: Databases were systematically searched using keywords ((mean platelet volume) OR mpv) AND (appendicitis). The inclusion criteria were all comparative studies of MPV in children aged less than 18 years and diagnosed with AA. Two authors independently assessed the methodological quality using the Downs and Black scale.
Results: We included fourteen studies in the final meta-analysis; most were retrospective. Eight studies compared the MPV values between AA and non-AA; four studies compared the same between AA and healthy controls; two studies compared the MPV values among all three groups. The estimated heterogeneity among the studies for all outcomes was high and statistically significant. The pooling the data showed no statistically significant difference in MPV (weighted mean difference (WMD) = -0.42, 95% CI = (-1.04, 0.20), p = 0.19) between AA and healthy controls or AA and non-AA cases (WMD = 0.01, 95% CI = (-0.15, 0.17), p = 0.90).
Conclusion: While MPV levels seem to have some utility in adult AA diagnosis, MPV levels should not dictate treatment options in pediatric AA.